Measurement of Personal PM10, PM2.5 and PM1.0 Exposures in Tractor and Combine Operations - Ali Aybek; Hasan Ekerbiçer; Selçuk Arslan (Journal of Agricultural Sciences)
The objective of this study was to determine the PM10, PM2.5, and PM1.0 exposure levels of tractor and combine harvester operators in rotary tilling, disc-harrowing, soil packing, planting, fertilizing, harvesting, hay making, and bale making and to determine PM-health effect on operators. The gravimetric method was used to determined PM concentrations. PM10 concentrations were higher than the threshold limit value (15000 µg m-³) determined by OSHA in rotary tilling (25770 µg m-³), wheat harvesting (29300 µg m-³), and hay making (24640 µg m-³).  Similarly, PM2.5 concentrations were also greater than the threshold limit (5000 µg m-³) in these operations (respectively with 5888, 10560, 8470 µg m-³). PM1.0 concentration was too high, especially in wheat harvest and hay making (respectively with 3130 and 6026 µg m-³), and was even greater than the PM2.5 threshold limit during hay making.  It is probable for such high PM concentrations of fine particles to increase the respiratory system nuisances. PM10 and PM2.5 concentrations were measured to be lower than the thresholds in all other field applications. A questionnaire was done on forty operators and upper and lower respiratory disturbances and smoking habits were determined. Sixty three percent of operators were smokers, and complain about coughing with 60% and phlegm with 83%. Health complaint about tightness in the chest is 31% and breathlessness is about 29%. Nevertheless, when smokers and non-smokers are evaluated separately, coughing rate decreases to 47% and tightness in the chest reduces to 13%. Although exposure to particulate matters is important in its effect on respiratory system disturbances, smoking habit aggravates the complaints. Operators need to use personal preventions to avoid such adverse health effects when operating tractors and combine harvesters without cabins. Operators are unlikely to work in the comfort zone due to high ambient temperature and low relative humidity in vehicles without cabins.